THE RESHAPING OF UNIVERSITY STUDENT AFFAIRS MANAGEMENT MECHANISM BASED ON ARTIFICIAL INTELLIGENCE TECHNOLOGY: INTEGRATION OF EDUCATIONAL THEORY AND CONSTRUCTION OF PSYCHOLOGICAL SUPPORT PATHWAYS - Li, Tao; Zhang , Xiao; Li, Cemei; Xiaoyan, Luo (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
With the rapid development of artificial intelligence (AI) technology, its application in university student affairs management has gradually deepened, driving the transformation of traditional management models toward intelligence, precision, and human-centeredness. Currently, university student management systems face many practical challenges, such as information fragmentation, delayed services, and weak psychological support mechanisms. These issues urgently need to be addressed through technological empowerment and theoretical innovation. Based on educational management theory, AI application theory, and psychological support models, this paper explores how AI technology can enhance the effectiveness of university student affairs management in aspects such as data integration, behavior analysis, early warning intervention, and decision support. At the same time, in line with the fundamental task of "moral education," the paper constructs an intelligent management mechanism that integrates ethical awareness, emotional warmth, and autonomous adaptability. The article focuses on analyzing the functional potential of generative AI in task processing, personalized services, and mental health support, reviewing the outcomes and limitations of domestic and international practical cases, and proposing a mechanism restructuring pathway that integrates educational goals, technological innovation, and psychological support systems. The study suggests that in the future, universities should strengthen the construction of a "human-machine-system" collaborative mechanism, break down data silos, enhance the work efficiency of counselors, and improve students' sense of fulfilment, ultimately achieving a comprehensive upgrade of the student affairs management system, centered on people and empowered by intelligence.